Attitudes of Mashhad Public Hospital's Nurses and Midwives toward the Causes and Rates of Medical Errors Reporting - Sedigheh Sedigh Mobarakabadi; Hosein Ebrahimipour; Ali Vafaie Najar; Roksana Janghorban; Fatemeh Azarkish (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Patient’s safety is one of the main objective in healthcare services; however medical errors are a prevalent potential occurrence for the patients in treatment systems. Medical errors lead to an increase in mortality rate of the patients and challenges such as prolonging of the inpatient period in the hospitals and increased cost. Controlling the medical errors is very important, because these errors besides being costly, threaten the patient’s safety. Aim: To evaluate the attitudes of nurses and midwives toward the causes and rates of medical errors reporting. Materials and Methods: It was a cross-sectional observational study. The study population was 140 midwives and nurses employed in Mashhad Public Hospitals. The data collection was done through Goldstone 2001 revised questionnaire. SPSS 11.5 software was used for data analysis. To analyze data, descriptive and inferential analytic statistics were used. Standard deviation and relative frequency distribution, descriptive statistics were used for calculation of the mean and the results were adjusted as tables and charts. Chi-square test was used for the inferential analysis of the data. Results: Most of midwives and nurses (39.4%) were in age range of 25 to 34 years and the lowest percentage (2.2%) were in age range of 55-59 years. The highest average of medical errors was related to employees with three-four years of work experience, while the lowest average was related to those with one-two years of work experience. The highest average of medical errors was during the evening shift, while the lowest were during the night shift. Three main causes of medical errors were considered: illegibile physician prescription orders, similarity of names in different drugs and nurse fatigueness. Conclusion: The most important causes for medical errors from the viewpoints of nurses and midwives are illegible physician's order, drug name similarity with other drugs, nurse's fatigueness and damaged label or packaging of the drug, respectively. Head nurse feedback, peer feedback, fear of punishment or job loss were considered as reasons for under reporting of medical errors. This research demonstrates the need for greater attention to be paid to the causes of medical errors.